1984
DOI: 10.1557/proc-35-439
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy and Defects in Laser-Irradiated, Single-Crystal Bismuth

Abstract: The (0001), (1010), and (2110) faces of Bi have been pulse laser melted at 0.5 J/cm2 with a Q-switched Ruby laser. Nomarski Interference Contrast Microscopy, Channeling, and selective chemical etching have been used to investigate the response to the laser irradiation. The response of the material and the level of damage is shown to be strongly correlated to the critical resolved shear stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…1,4,5 Since various crystal surface orientations possess different densities of surface atoms, different surface energies, and potential bonding sites, 6,7 which may influence the thermal and mechanical response of these surfaces, one can assume that crystal orientation may also play a role in the course of laser-material interaction. [8][9][10] Consequently, the subsequent material relaxation and henceforward the formation of periodic structures may also vary depending on the crystal orientation of the irradiated target. It has been found that silicon crystal orientation influences the final surface morphology under multiple-pulse irradiation, with (100) plane exhibiting the least tendency to form conical structures.…”
mentioning
confidence: 99%
“…1,4,5 Since various crystal surface orientations possess different densities of surface atoms, different surface energies, and potential bonding sites, 6,7 which may influence the thermal and mechanical response of these surfaces, one can assume that crystal orientation may also play a role in the course of laser-material interaction. [8][9][10] Consequently, the subsequent material relaxation and henceforward the formation of periodic structures may also vary depending on the crystal orientation of the irradiated target. It has been found that silicon crystal orientation influences the final surface morphology under multiple-pulse irradiation, with (100) plane exhibiting the least tendency to form conical structures.…”
mentioning
confidence: 99%